1978
DOI: 10.1111/j.1469-8749.1978.tb15179.x
|View full text |Cite
|
Sign up to set email alerts
|

Heredofamilial Brachial Plexus Neuropathy (Hereditary Neuralgic Amyotrophy with Brachial Predilection) in Childhood

Abstract: SUMMARY Three families with a total of at least 12 members affected by heredo‐familial brachial plexus neuropathy (hereditary neuralgic amyotrophy) are described, and three affected boys (age‐range 4 to 7 years 10 months) are reported in detail. All three children had recurrent episodes of pain in the shoulders and arms, followed by weakness and wasting of affected muscles. Subsequently there was gradual recovery. All three had close‐set eyes, and affected relatives usually had a similar physiognomy. Case 1 ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

1980
1980
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(11 citation statements)
references
References 26 publications
1
10
0
Order By: Relevance
“…The dysmorphic features of our patients were only slight. However, they had a narrow face and hypotelorism and did indeed show the resemblance to portraits by Modigliani pointed out by Dunn et al (1978).…”
supporting
confidence: 61%
See 2 more Smart Citations
“…The dysmorphic features of our patients were only slight. However, they had a narrow face and hypotelorism and did indeed show the resemblance to portraits by Modigliani pointed out by Dunn et al (1978).…”
supporting
confidence: 61%
“…The hereditary form has a greater tendency to start in childhood (Dunn et al 1978), although both HNA and the sporadic form most commonly occur in the third and fourth decade (Windebank 1984). Patient 1 had his first attack when he was 15 years old.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…NA is more common in men than in women, occurring in a ratio of about 2:1, and it can affect people of all ages, with a median onset age of around 40 years for the idiopathic form and around 25 years for the hereditary form . Several reports have described the disorder in children and newborns, with the latter often seeming to show an association with a concomitant osteomyelitis of the humerus …”
Section: Epidemiologymentioning
confidence: 99%
“…4 Several reports have described the disorder in children and newborns, with the latter often seeming to show an association with a concomitant osteomyelitis of the humerus. [16][17][18][19][20] Recurrent episodes occur in a significant proportion of patients, with at least 25% of idiopathic cases and 75% of hereditary cases having a second episode during the first years after their initial attack. 4 In our clinical practice, over the last 20 years, we found that recurrences occur even more often, and they seem to be a common feature of the disorder.…”
Section: Epidemiologymentioning
confidence: 99%